Efficacy of submucosal administration of tramadol on acute pain following third molar surgery: a systematic review and meta-analysis - Ahmad Salem Assari; Elaf Mubarak Abdullah Algharbi; Abdulmajeed Mohammed Abuhabsha; Basel Basheer Alshammry; Yosef Aeed Alanazi; Reem Abdulaziz Abuhaimed; Ali Mohammad Ali Alzahrani; Abdulrahaman Saud Alduhaim (Frontiers Media S.A., 2024)
ObjectivesThis systematic review aimed to assess the effectiveness of submucosal tramadol injections in post-operative pain management following third molar surgical extraction.Materials and methodsDatabases, such as PubMed, Scopus, ScienceDirect, and Cochrane Library, were systematically searched using relevant keywords. Randomized clinical trials that met the inclusion criteria were assessed to determine the effectiveness of tramadol in managing acute post-operative pain following third molar surgery.ResultsIn total, seven studies with participants of 18 and over following randomized placebo-controlled trials were considered for the analysis. A submucosal injection of 2 ml (50-100 mg) of tramadol adjacent to the impacted mandibular third molar effectively controlled pain for up to 6-24 h following surgery. Non-serious adverse events, such as nausea, vomiting, and headache, were reported in two studies. Meta-analysis (subgroup analysis) revealed heterogeneity among the studies, demonstrating variability in the results across the included studies. In addition, tramadol demonstrated a significant decrease in post-operative pain.ConclusionSubmucosal tramadol is an efficient, safe, and dependable method for reducing post-operative acute pain, particularly in the first 6 h following impacted third molar surgery. However, due to the observed heterogeneity in the research, there is need for cautious interpretation of the findings and potential limitations in the evidence base. To enhance the quality of evidence on this topic, we strongly recommend conducting new RCTs using established methodologies.Clinical relevancePost operative pain following third molar surgeries is one of the common complications. Submucosal tramadol injections were found to be successful in reducing post extraction pain as well as other morbidities.